Gallbladder agenesis in a patient with choledochoduodenal fistula, report of an exceptional case - Parra, Samuel Raul Medina; Sánchez, Omar Sosa; Ibarra, Rodrígo Migoya; Barrientos, Cheryl Zilahy Díaz; Gandarillas, Carlos Alberto Martínez; González, José Miguel Espinosa (International Journal of Research in Medical Sciences, 2023)
Vesicular agenesis refers to the congenital absence of the gallbladder, however, vesicular agenesia is a very scarce condition worldwide, so there is little information available on its clinical presentation and surgical data. This is a 79-year-old male patient, with a history of diabetes mellitus of long evolution, without a surgical history, who comes for colic pain of 15 days of evolution in right hypochondrium, as well as unquantified fever and jaundice, during its initial evaluation in the emergency room para clinics were requested observing leukocytosis, hyperbilirubinemia and elevation of liver enzymes, ultrasound of liver and bile ducts reported common anatomical situation gallbladder, occupied entirely by multiple hyperechogenic images, configuring sign of W.E.S. and common bile duct of 7.2 mm, concluding gallbladder scleroatrophic and vesicular agenesia during trans-surgery. Vesicular agenesis is an extremely rare condition that is mostly diagnosed during surgery, which can lead to erroneous diagnosis and unnecessary surgery in patients with symptoms including biliary colic, choledocholithiasis with or without cholangitis, and an ultrasound showing a scleroatrophic gallbladder. Surgeons In situations where there is clinical evidence consistent with biliary colic in a context of gallbladder agenesis, and the symptoms persist without finding any other cause, a surgical approach to release adhesions could be considered; since, as observed, this may result in improved symptoms, although the explanation is not yet completely clear.